2016
DOI: 10.3389/fmars.2016.00258
|View full text |Cite
|
Sign up to set email alerts
|

Microzooplankton Stoichiometric Plasticity Inferred from Modeling Mesocosm Experiments in the Peruvian Upwelling Region

Abstract: Oxygen minimum zones (OMZs) are often characterized by nitrogen-to-phosphorus (N:P) ratios far lower than the canonical Redfield ratio. Whereas, the importance of variable stoichiometry in phytoplankton has long been recognized, variations in zooplankton stoichiometry have received much less attention. Here we combine observations from two shipboard mesocosm nutrient enrichment experiments with an optimality-based plankton ecosystem model, designed to elucidate the roles of different trophic levels and element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
5
1
Order By: Relevance
“…Elser et al (2000) stated that "Stoichiometric theory predicts that homeostatic herbivores consuming elementally imbalanced food will exhibit strongly diminished efficiency of conversion of ingested carbon into new biomass." Also, Marki and Pahlow (2016) reported, somewhat in contrast with previous views that put greater emphasis on polyunsaturated fatty acid and the N and P content (Andersen & Hessen, 1991;Elser et al, 2000;Giordano, 2013;Giordano et al, 2015), that the N:C ratio of prey biomass has a strong influence on microzooplankton nutrition. Further work is needed on the effect of nutrition (Støttrup & Jensen, 1990), and on the interaction of quality of the algal food and algal toxins on the life cycle (Prince et al, 2006;Turner, Ianora, Miralto, Laabir, & Esposito, 2001), on the entire life cycle of the grazer.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Elser et al (2000) stated that "Stoichiometric theory predicts that homeostatic herbivores consuming elementally imbalanced food will exhibit strongly diminished efficiency of conversion of ingested carbon into new biomass." Also, Marki and Pahlow (2016) reported, somewhat in contrast with previous views that put greater emphasis on polyunsaturated fatty acid and the N and P content (Andersen & Hessen, 1991;Elser et al, 2000;Giordano, 2013;Giordano et al, 2015), that the N:C ratio of prey biomass has a strong influence on microzooplankton nutrition. Further work is needed on the effect of nutrition (Støttrup & Jensen, 1990), and on the interaction of quality of the algal food and algal toxins on the life cycle (Prince et al, 2006;Turner, Ianora, Miralto, Laabir, & Esposito, 2001), on the entire life cycle of the grazer.…”
Section: Discussioncontrasting
confidence: 71%
“…This observation may be relevant to our discussion because it has been shown that a lower C:N ratio has a strong positive influence on copepods growth (Touratier, Legendre, & Vézina, 1999) and that copepods growth efficiency in terms of N is typically higher than that in terms of C (Jones & Flynn, 2005;Støttrup & Jensen, 1990). Also, Marki and Pahlow (2016) reported, somewhat in contrast with previous views that put greater emphasis on polyunsaturated fatty acid and the N and P content (Andersen & Hessen, 1991;Elser et al, 2000;Giordano, 2013;Giordano et al, 2015), that the N:C ratio of prey biomass has a strong influence on microzooplankton nutrition. Also, Marki and Pahlow (2016) reported, somewhat in contrast with previous views that put greater emphasis on polyunsaturated fatty acid and the N and P content (Andersen & Hessen, 1991;Elser et al, 2000;Giordano, 2013;Giordano et al, 2015), that the N:C ratio of prey biomass has a strong influence on microzooplankton nutrition.…”
Section: Discussionmentioning
confidence: 76%
“…Optimality-based modeling in combination with trait/trade-off based modeling is a promising approach in this direction (Smith et al 2011(Smith et al , 2014 and has been applied to the global scale for phytoplankton (Arteaga et al 2014). For zooplankton, few optimality-based models exist (Pahlow and Prowe 2010;Visser and Fiksen 2013;Marki and Pahlow 2016;Su et al 2018) and none have been applied globally.…”
Section: Food Web Structure and Ecosystem Functionsmentioning
confidence: 99%
“…, Boersma et al. , Marki and Pahlow ). The amount of fatty acids, and especially of polyunsaturated fatty acids (PUFA), in the algae also seems to be crucial for their consumers (Mueller‐Navarra , Rossoll et al.…”
Section: Hypothesesmentioning
confidence: 97%
“…What makes an algal cell more or less palatable to selective feeders, however, is still a matter of debate and may depend on the grazer's life stage and physiological state (e.g., Sterner and Robinson 1994). High ratios between C and other nutrients (especially N and P) may be an indication of low biomass quality for grazers (Checkley 1980, L€ urling and Van Donk 1997, Touratier et al 1999, Sterner and Elser 2002, Hessen et al 2007, Malzahn et al 2007, Boersma et al 2008, Marki and Pahlow 2016. The amount of fatty acids, and especially of polyunsaturated fatty acids (PUFA), in the algae also seems to be crucial for their consumers (Mueller-Navarra 1995, Rossoll et al 2012); copepods, for example, depend on their diet for the essential supply of x3 PUFAs, which they cannot synthetize (Fraser et al 1989, Støttrup andJensen 1990).…”
mentioning
confidence: 99%